2005
DOI: 10.1021/es048548j
|View full text |Cite
|
Sign up to set email alerts
|

Sorption Enhancement of Aromatic Sulfonates onto an Aminated Hyper-Cross-Linked Polymer

Abstract: A macroreticular resin adsorbent CHA-101 was aminated by dimethylamine, and a novel sorbent named M-101 was obtained. Several industrially important aromatic sulfonates including sodium benzenesulfonate (BS), sodium p-toluenesulfonate (TS), and sodium 2-naphthalenesulfonate (NS) were selected as general solutes to evaluate the performance of the newly synthesized resin particles. X-ray photoelectron spectroscope (XPS) analyses was used to determine the protonation degree of amino group at different solution pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 18 publications
2
94
0
Order By: Relevance
“…As discussed in the sub-section on multistage polymerizations, particles can swell to a great extent by absorbing hydrophobic species. This can be used for removing undesired species either from water [413][414][415][416] or from organic media [417]. Moreover, gaseous species can also be absorbed by particles [418][419][420].…”
Section: Ion-exchange Catalysis and Scavengingmentioning
confidence: 99%
“…As discussed in the sub-section on multistage polymerizations, particles can swell to a great extent by absorbing hydrophobic species. This can be used for removing undesired species either from water [413][414][415][416] or from organic media [417]. Moreover, gaseous species can also be absorbed by particles [418][419][420].…”
Section: Ion-exchange Catalysis and Scavengingmentioning
confidence: 99%
“…The other reagents and solvents were commercially available and used without purification. 1 H NMR spectra were recorded on a Varian UNITY plus 400 MHz NMR spectrometer. Infrared (IR) spectra were recorded on a BIO-RAD FTS-6000 spectrometer in the range of 4000 -290 cm -1 .…”
Section: Materials and Instrumentsmentioning
confidence: 99%
“…The residue was purified by column chromatography (SiO 2 , 100:1 dichloromethane/methanol) to give 2-acryloylamidopyridine as a yellow solid (4.38 g, 61%). 1 + m/z = 149.28.…”
Section: Preparation Of 2-acryloylamidopyridine (M1)mentioning
confidence: 99%
“…aromatic compounds [14,15]. In addition, study of the adsorption mechanism revealed that the improved polarity of the hyper-crosslinked resin plays an important role in the enhanced adsorption of the hyper-cross-linked resin toward polar aromatic compounds [16,17].…”
Section: Introductionmentioning
confidence: 99%